A study of the effect of personality on the moods of young adult learners - Panchu, Pallavi; Ali, Syed Liyakath; Thomas, Tom (International Journal of Research in Medical Sciences, 2016)
Background: Medical education is inherently stressful and can be a source of anxiety and depression if a student fails to cope with the vast syllabus. The personality of the learner, if apt, will help him perform better as a student and doctor. It would also act as a stabilizing influence on the moods of the learners while facing academic challenges. This study was done to analyse the effects of personality on the moods, namely stress, anxiety and depression levels. Methods: The study was done using validated tools, the big 5 personality and the depression, anxiety and stress scale questionnaire (DASS). The study sample consisted of 200 first and second year medical students in an Indian medical college. ANOVA and Pearson’s correlation tests were used. Results: The results show that personality traits have a highly positive influence on development of stress, anxiety and depression and no influence of gender noted. Conclusions: In addition to academic scores, personality testing may be advised before the student gains entry into the medical profession.